2009
DOI: 10.1097/cji.0b013e318195b59e
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 2-mediated Conversion of Ovarian Cancer-associated CD4+ Regulatory T Cells Into Proinflammatory Interleukin 17-producing Helper T Cells

Abstract: Epithelial ovarian cancer (EOC) is a highly inflammatory malignancy, characterized by the presence, at the tumor site, of regulatory T cells (Treg) that suppress antitumor immunity. Recently, a new lineage of CD4+ T cells producing the proinflammatory cytokine interleukin (IL)-17 [T helper (TH) 17] has been identified as a major player in some autoimmune diseases. The role of TH17 cells in cancer, however, and their relationship with coexisting Treg populations, whose differentiation is partially controlled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 38 publications
3
39
1
Order By: Relevance
“…Plasticity has been demonstrated in the tumor microenvironment (33), and our data extend this finding to the environment of the allogeneic endothelium under inflammatory conditions such as those observed following organ transplantation.…”
Section: Foxp3supporting
confidence: 83%
See 1 more Smart Citation
“…Plasticity has been demonstrated in the tumor microenvironment (33), and our data extend this finding to the environment of the allogeneic endothelium under inflammatory conditions such as those observed following organ transplantation.…”
Section: Foxp3supporting
confidence: 83%
“…HMEC-1 was provided by A. Kesikli (University of Regensburg, Germany) and used between passages eight and 15 (33). Primary ECs (i.e., HDMECs; Lonza) were used between passages three and six (34,35).…”
Section: Methodsmentioning
confidence: 99%
“…Th is result adds a new COLON/SMALL BOWEL Human Gliadin-Specific Th17 Cells from Treg cells becoming Th 17 cells, as this population does not retain any of the characteristics of Treg cells, with the exception of its ability to produce TGF β ( 48,49 ). However, our data do not formally exclude this possibility, which needs to be further explored in detail in CD.…”
Section: Human Gliadin-specific Th17 Cellscontrasting
confidence: 54%
“…Leveque et al showed that doses of IL-2 converted CD4C regulatory cells into IL-17 secreting helper T-cells that potentially lost their regulatory activity in ovarian cancer tumor specimens. 128 Lymphodepletion prior to TIL based adoptive immunotherapy has greatly improved the success rate in metastatic melanoma treatment [58][59][60] and extends in-vivo survival of transferred TILs. 129 Some authors suggest that profound lymphoablation with stem-cell rescue may further enhance immunotherapies in cancer, and have shown significant results in animal models, although they caution about adopting this method into clinical practice.…”
Section: Immune Checkpoint Inhibitors and Agonists In Ovarian Cancermentioning
confidence: 99%